PERSPEKTIF POLITIK DESENTRALISASI DALAM PEMBANGUNAN KAWASAN PERBATASAN DI KABUPATEN SANGGAU, KALIMANTAN BARAT - Saherimiko Saherimiko (Indonesian Journal of Dialectics, 2012)
This research is conducted to find out the causal factor soft the non optimal and retardation of the development of the borderarea in the Sanggau regency which was done by the government, seen from the perspective of the political decentralization. This research is aimed to describe and analyze the implementation of the political decentralization and the roles of central and local government's in the border area development with its determinant factors. The research uses qualitative research design. Library study, observation and purposive sampling interview are used as the data collection technique. Furthermore, the data is validated by using data reduction, data display ,triangulation, verification, and inference which is analyzed qualitatively. The basic theory and analysis in this research is the theory of decentralization in which giving/delivering power and authority from central government to the local government; such as political, fiscal, and administrative authorities. This term refers to the decentralization in the development field, its form can be in deconcentration and devolution. The result of the research shows that the development of the border area done by the government is not yet optimal. One of its indicators is the lack of basic infrastructure in Sanggau regency. However, there are some supporting factors in the development of the border area such as strategic geographical location, natural resources potential, and the support from local communities. In other hand, the constraint factors are the lack of potential will, government's commitment, limited financial budget, investment climate that is relatively less conducive, low quality of human resources, the local products that have not been competitive yet, and no laws and legal institution that are needed.